Australian Institute of Sport (2000)
The Australian Institute of Sport (AIS) leads the development of elite sport and is widely acknowledged in Australia and internationally as a world best practice model for elite athlete development. The AIS is a pre-eminent elite sports training institution in Australia with world class facilities and support services.